2018
DOI: 10.4314/njbas.v25i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Free Radical Scavenging Potentials of N-Hexane and Ethyl Acetate Fractions of <i>Phyllanthus Fraternus</i>

Abstract: The genus Phyllanthus (Phyllantaceae) is widely used in the african system of traditional medicine and is reported to have various biological activities. In this study, antimicrobial and antioxidant activities of nhexane and ethyl acetate fractions of Phyllanthus fraternus leaves were investigated. The antimicrobial screening was carried out against Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Pseudomonas aeruguinosa, Salmonella typhi and Klebsiella pneumoniae, using Agar-well diffusion method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
3
13
1
Order By: Relevance
“…Citrus sinensis also produced considerable decontamination of the microbial load from the stream water, However, the stem and seed material significantly (p<0.05) reduced the amount of the bacteria count but could not attend complete elimination, even at the highest doses (0.5 g/l) (Table 3). This finding reflect increased concentration of antimicrobial agent as the treatment dose increased, this is in line with the findings of Yusuf et al, [38], Tsado et al, [39], Ibrahim et al, [40], who reported that increased in concentration of plant material resulted in corresponding decreased in bacterial load. This finding is in line with the previous studies that reported that Citrus sinensis, Citrus aurantifolia and Citrus limon showed a very good antimicrobial activity against E. coli, S. typhi, B. subtilis, K. pnemonia and S. aureus [41].…”
Section: Discussionsupporting
confidence: 90%
“…Citrus sinensis also produced considerable decontamination of the microbial load from the stream water, However, the stem and seed material significantly (p<0.05) reduced the amount of the bacteria count but could not attend complete elimination, even at the highest doses (0.5 g/l) (Table 3). This finding reflect increased concentration of antimicrobial agent as the treatment dose increased, this is in line with the findings of Yusuf et al, [38], Tsado et al, [39], Ibrahim et al, [40], who reported that increased in concentration of plant material resulted in corresponding decreased in bacterial load. This finding is in line with the previous studies that reported that Citrus sinensis, Citrus aurantifolia and Citrus limon showed a very good antimicrobial activity against E. coli, S. typhi, B. subtilis, K. pnemonia and S. aureus [41].…”
Section: Discussionsupporting
confidence: 90%
“…There are many reports that support the use of antioxidant supplement in reducing the level of oxidative stress and in preventing the development of complication associated with disease [36,22]. In this study the methanol leaves extract of Eucalyptus calmaldulensis exhibited antioxidant property as confirmed by DPPH antioxidant assay.…”
Section: Discussionsupporting
confidence: 51%
“…Minimum inhibitory concentration (MIC) is the lowest concentration of an extract that inhibit the visible growth of the test organism after 24hrs incubation [31][32][33]. The low MIC value (1.28) obtained for both S. aureus and S. pyogenes indicate that small quantity of the extract is needed to inhibit both organisms.…”
Section: Discussionmentioning
confidence: 99%